Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Kiel, Steffen, Sami, Marco, Taviani, Marco (2023): Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions. European Journal of Taxonomy 910: 115-160, DOI:10.5852/ejt.2023.910.2365, URL: https://europeanjournaloftaxonomy.eu/index.php/ejt/article/download/2365/10359